Efficacy of immune checkpoint inhibitor therapy in EGFR mutation-positive patients with NSCLC and brain metastases who have failed EGFR-TKI therapy - Zhou, Shujie; Ren, Fei; Meng, Xiangjiao (Frontiers in Immunology, 2022)
Background Few treatment options are available for brain metastases (BMs) in EGFR-mutant non-small cell lung cancer (NSCLC) that progress with prior EGFR tyrosine kinase inhibitor (EGFR-TKI) therapy. This study aimed to evaluate the efficacy of immune checkpoint inhibitor (ICI) therapy in these patients. Methods NSCLC patients with confirmed sensitive EGFR mutations and BMs were retrospectively reviewed. All patients experienced failure of EGFR-TKI therapy and were divided into two cohorts based on subsequent treatment. Cohort 1 included patients who received ICI therapy, while cohort 2 included patients treated with chemotherapy. Overall and intracranial objective response rates (ORRs) were used to evaluate the treatment response. Overall and intracranial progression-free survival (PFS) were calculated by Kaplan‒Meier analysis and compared with the log-rank test. Univariate and multivariate Cox analyses were used to identify prognostic factors. Results A total of 53 patients treated with ICI therapy and 40 patients treated with chemotherapy were included in cohorts 1 and 2, respectively. In cohort 1, the overall ORR was 20.8%, with a median overall PFS of 4.2 months. The median intracranial PFS was 5.1 months. Of the 38 patients with measurable intracranial lesions, the intracranial ORR was 21.0%. Patients who received ICI combined with chemotherapy had the highest intracranial ORR of 37.5%. Compared to patients treated with chemotherapy in cohort 2, patients receiving ICI combined with chemotherapy had both longer intracranial PFS (6.4 vs. 5.1 months, p = 0.110) and overall PFS (6.2 vs. 4.6 months, p = 0.054), and these differences approached statistical significance. Univariate and multivariate Cox analyses demonstrated that high disease burden (p = 0.019), prior third-generation EGFR-TKI therapy (p = 0.019), and a poor lung immune prognostic index (LIPI) (p = 0.012) were independent negative predicators of overall PFS and that multiple BMs were negatively correlated with intracranial PFS among patients treated with ICI therapy. Conclusions Our results suggested that ICI combined with chemotherapy had potent intracranial efficacy and may be a promising treatment candidate in EGFR-mutant NSCLC patients with BMs for whom prior EGFR-TKI therapy failed.